Strategic guidelines for the digital transformation of modern education - Elena Alexandrovna Panina (Вестник Майкопского государственного технологического университета)
The importance of the digital transformation of an educational institution is due to global trends in the spread of digital tools in all spheres of public life. The digital environment today is the most powerful driver of educational services, changing its content, technological and organizational content. The study of the main strategic guidelines for the digital transformation of an educational institution will help deepen further research in the direction of solving the problematic issues of introducing digital tools in this area, which actualizes the feasibility of the research. The research problem is: what are the main strategic guidelines for the digital transformation of modern education as a driver for the promotion of educational services? The purpose of the research is to identify relevant guidelines for the introduction of digital tools in the field of education. The methodological basis of the study is the general scientific cognition methods: analysis of sources in the eLibrary, generalization.The results of the study are the following: analysis of the content of the concept of "digital transformation of education" has made it possible to clarify its characteristics (digital service as an environment, digital service as a process), to identify structural components (digital tools, digital educational technologies, digital traces as the results of educational and pedagogical activities), to identify strategic landmarks of education in modern conditions (digital university, digital education, digital campus, digital stakeholders).The key conclusions are the digital model of higher education is the most powerful driver of educational services in the modern digital space and the beginning of a new digital paradigm.